Complete remission in an elderly patient with non-small cell lung cancer and brain metastasis using immunotherapy plus chemotherapy: a clinical case - A. Chehal; A. ALakkad; H. Alkaabi; A. A. Razek; Y. Z. Alabed; H. M. Almasarei (Сеченовский вестник)
Lung cancer remains a leading cause of cancer-related mortality, with non-small cell lung cancer (NSCLC) accounting for the majority of cases. Among its subtypes, adenocarcinoma is most prevalent. Stage IV NSCLC comes with a poor prognosis, particularly in elderly patients with comorbidities. Programmed death-ligand 1 (PD-L1) checkpoint inhibitors have demonstrated promising efficacy, including in cases with brain metastases.Case report. The case concerns an 83-year-old woman with diabetes mellitus, arterial hypertension, and atrial fibrillation, diagnosed with stage IVB poorly differentiated lung adenocarcinoma which was confirmed by a percutaneous lung biopsy. PD-L1 expression was 40%. Magnetic resonance imaging identified a solitary brain metastasis. The patient was treated with dexamethasone and a CheckMate 9LA protocol was initiated with reduced-dose carboplatin, pemetrexed, nivolumab, and ipilimumab. A two years follow-up positron emission tomography showed a significant reduction in lung cancer. The brain lesions had almost disappeared, and in addition a clinical improvement could be observed.Discussion. This case underscores the potential for durable remission and improved quality of life through individualized treatment strategies in older patients with advanced NSCLC and brain involvement